2014
DOI: 10.1001/jamafacial.2014.351
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Oral Celecoxib for Acute Postoperative Pain in Face-lift Surgery

Abstract: ace-lift or rhytidectomy is a cornerstone procedure in facial rejuvenation and is rising in popularity. 1 While most patients generally report positive overall experiences, elevated pain levels and accompanying opioid consumption can potentially hinder an otherwise excellent surgical effort and outcome. 2,3 Despite the known adverse effects of nausea, vomiting, dizziness, drowsiness, sedation, pruritus, and urinary retention associated with opioid analgesics, they are an established tool in controlling postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…COX-2 is a proinflammatory product of TLR4-mediated immune signaling (Cao et al, 1997;Zhang et al, 2008;Czapski et al, 2010;Tse et al, 2014;Gaikwad and Agrawal-Rajput, 2015). Both preclinical and clinical studies indicate that coadministration of COX-2 inhibitors (e.g., celecoxib) with morphine significantly potentiates the resulting pain relief in both sexes (Vaughan et al, 1997;Deciga-Campos et al, 2003;Pinardi et al, 2005;Reuben and Ekman, 2005;Aynehchi et al, 2014). Similarly, in studies of women after gynecological surgery, treatment with the COX-2-selective inhibitor rofecoxib significantly attenuated both surgical pain and opioid consumption (Sinatra et al, 2006), whereas treatment with parecoxib was associated with a lower incidence of postoperative headache and greater overall satisfaction compared with placebo (Luscombe et al, 2010).…”
Section: Clinical Findings Support An Immune-based Treatment For Womenmentioning
confidence: 99%
“…COX-2 is a proinflammatory product of TLR4-mediated immune signaling (Cao et al, 1997;Zhang et al, 2008;Czapski et al, 2010;Tse et al, 2014;Gaikwad and Agrawal-Rajput, 2015). Both preclinical and clinical studies indicate that coadministration of COX-2 inhibitors (e.g., celecoxib) with morphine significantly potentiates the resulting pain relief in both sexes (Vaughan et al, 1997;Deciga-Campos et al, 2003;Pinardi et al, 2005;Reuben and Ekman, 2005;Aynehchi et al, 2014). Similarly, in studies of women after gynecological surgery, treatment with the COX-2-selective inhibitor rofecoxib significantly attenuated both surgical pain and opioid consumption (Sinatra et al, 2006), whereas treatment with parecoxib was associated with a lower incidence of postoperative headache and greater overall satisfaction compared with placebo (Luscombe et al, 2010).…”
Section: Clinical Findings Support An Immune-based Treatment For Womenmentioning
confidence: 99%
“…The impact that inadequate analgesia harbors on quality of life, hospital readmission rates, length of stay, and by extension, healthcare costs, has spurred renewed interest regarding the use of non‐opioid agents . In our current healthcare environment and with recognition of the opioid crisis, increasing awareness regarding the misuse and escalation of prescriptions drugs has led to a nationwide search for effective alternatives . Immediate aggressive postoperative analgesia is thought to reduce subsequent analgesic requirements due to its effect on inflammatory cytokines, as well as alleviate anxiety and other pain‐associated complications .…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with prior otolaryngology studies evaluating celecoxib. 24,25 We have also demonstrated that using COX-2 inhibitors may decrease the amount of opioids used postoperatively by patients with HNC.…”
Section: Discussionmentioning
confidence: 90%